Hilar/endobronchial NUT midline carcinoma: A case report - Deepika Sirohi, MD; Sumit Mamun, MD, FACP; Jaishree Jagirdar, MD (Elsevier, 2017)
Nuclear protein of the testis (NUT) midline carcinoma (NMC) is a rare aggressive tumor described in the midline in the chest and head and neck. Initially reported in younger individuals, it has subsequently been shown to have a wider age distribution. The defining feature of these tumors is its association with BRD-NUT rearrangements. Occasionally NMC has been observed in a non-midline location. This case report describes an unusual rapidly progressing non-midline hilar/endobronchial location of an NMC in a 34-year-old man. The clinical and histologic features were that of an undifferentiated neoplasm concerning for a small cell carcinoma or a lymphoma. A broad panel of immunohistochemical markers for carcinoma, lymphoma and melanoma were negative which led us to suspect a diagnosis of NMC. A positive immunostaining with p63 and NUT protein antigen confirmed the diagnosis. The p63 positivity and cytokeratin negativity suggest a primitive/precursor squamous cell derivation. Keywords: Nuclear protein in testis midline carcinoma, Hilar/endobronchial